Value of latest-generation cone-beam computed tomography for post lipiodol-embolization imaging in hepatic transarterial chemoembolization in comparison with multi-detector computed tomography: original investigation - Alizadeh, Leona Soraja; Koch, Vitali; Vogl, Thomas J.; Yel, Ibrahim; Gruenewald, Leon; Albrecht, Moritz H.; Herrmann, Eva; Knebel Doeberitz, Philipp L. von; Booz, Christian (Academic radiology, 2022)
Rationale and Objectives - To evaluate image quality, radiation dose (phantom study) and tumor volumetry of intraprocedural cone-beam computed tomography (CBCT) compared to postprocedural multidetector computed tomography (MDCT) in patients undergoing hepatic conventional transarterial chemoembolization (cTACE). - Materials and Methods - One hundred fourteen patients (64/50 female/male; mean age, 57 ± 14 years) who had undergone cTACE including intraprocedural-CBCT and postprocedural-MDCT were retrospectively enrolled. Subjective image quality (IQ) and suitability for assessing Lipiodol distribution were compared using 4-point Likert scales; additionally, lesion to liver contrast (LLC) and contrast-to-noise-ratio (CNR) were compared. Tumor volumes were measured semi-automatically and compared to magnetic resonance imaging (MRI). Effective doses were measured using an anthropomorphic phantom. - Results - The suitability of CBCT for assessing Lipiodol distribution during cTACE was comparable to MDCT (mean score, 3.2 ± 0.6) and CBCT (3.4 ± 1.0, p = 0.29). Subjective overall IQ was rated with a mean score of 3.2 ± 0.7 (κ = 0.66) in CBCT and 3.1 ± 0.4 (κ = 0.57, p = 0.15) in MDCT. Evaluation of LLC showed significant differences between CBCT and MDCT (mean scores 3.6 ± 1.2 and 2.6 ± 1.5, respectively). CNR analysis demonstrated comparable mean values for CBCT and MDCT (3.5 ± 1.3 vs. 3.4 ± 1.8, p = 0.31). No significant differences were found regarding tumor volumetry (mean volumes: CBCT, 27.0 ± 17.4 mm3; MDCT: 26.8 ± 16.0 mm3; p = 0.66) in comparison to T2-weighted MRI (25.9 ± 17.6 mm3). Effective doses were 3.2 ± 0.6 mSv (CBCT) and 2.5 ± 0.3 mSv (MDCT) (p < 0.001). No cTACE-related complications (bleeding, non-target embolization) were missed on intraprocedural CBCT in comparison to postprocedural MDCT. - Conclusion - Latest-generation intraprocedural CBCT provides suitable assessment of Lipiodol distribution and similar image quality compared to MDCT while allowing for robust volumetric tumor measurements and immediate complication control by visualizing non-target embolization and hematoma. Therefore, it may improve patient safety and outcome as well as clinical workflow compared to postprocedural MDCT in hepatic cTACE in certain cases.